Assessment of Polycyclic Aromatic Hydrocarbon Exposure in Trainee Firefighters Using PAH CALUX Bioassay - Johanna Grünfeld; Peter Møller; Ulla Vogel; Simon Pelle Jensen; Vivi Kofoed-Sørensen; Maria Helena Guerra Andersen (Toxics)
This work investigated the application of a reporter gene bioassay in assessing polycyclic aromatic hydrocarbon (PAH) exposure in trainee firefighters. In the PAH CALUX bioassay, the PAH-induced activation of the aryl hydrocarbon receptor in a reporter cell line is recorded by increased luminescence. A repeated measurement study was performed, collecting urine and skin wipe samples at two baseline sessions (spring and autumn) and after three firefighting sessions: one with wood fuel, one with gas fuel, and one without fire. The bioassay response was expressed as benzo[a]pyrene equivalents, which was compared to levels of 16 EPA criteria PAHs in skin wipe samples and 8 hydroxylated PAHs (OH-PAHs) in urine samples quantified by chromatography–tandem mass spectrometry techniques. Benzo[a]pyrene equivalents and PAH levels in skin wipes indicated larger exposure to PAHs during the wood session compared to the other sessions. The urine bioassay showed non-significant effect sizes after all sessions, whereas the chemical analysis showed increased OH-PAH levels after the gas session. The non-significant changes observed for the session without fire suggest a negligible exposure from contaminated gear. In conclusion, the bioassay response for skin wipes shows that trainee firefighters were exposed to higher levels of potentially toxic PAHs during the wood fire training session.